Review: Natural products isolated from Portulaca oleracea (purslane, Ma-Chi-Xian): Focus on oleraciamides and oleracones - CHRISTIAN BAILLY (Smujo International, 2021)
Abstract. Bailly C. 2021. Review: Natural products isolated from Portulaca oleracea (purslane, Ma-Chi-Xian): Focus on oleraciamides and oleracones. Nusantara Bioscience 13: 202-210. Portulaca oleracea L., purslane in English and Ma-Chi-Xian in Chinese, is largely used in traditional medicine to treat various diseases and conditions, including dysentery and urinary tract dysfunctions, and post-partum bleeding. It is also an edible plant with high nutritional potential. Extracts of P. oleracea display antioxidant, anti-inflammatory, and antiproliferative activities, associated with numerous bioactive secondary metabolites, including alkaloids, terpenoids, lignans, and polysaccharides. The present review focuses on two sub-groups of natural products isolated in recent years from P. oleracea: the alkaloids oleraciamides A-to-G and the oleracones A-to-L, which are mostly flavonoids. Their structural diversity and pharmacological properties, described in recent publications and patents, have been analyzed. These two subgroups of natural products deserve additional studies to delineate their mechanism of action. In addition, they could serve as a starting point for the design of novel anti-inflammatory agents, at least for some of them. This review provides a global view of these compounds, which is necessary to promote further phytochemical studies and better apprehend the traditional use of the plant and its extracts.